Identification of Novel Antisense-Mediated Exon Skipping Targets in DYSF for Therapeutic Treatment of Dysferlinopathy - Joshua J.A. Lee; Rika Maruyama; William Duddy; Hidetoshi Sakurai; Toshifumi Yokota (Elsevier, 2018)
Dysferlinopathy is a progressive myopathy caused by mutations in the dysferlin (DYSF) gene. Dysferlin protein plays a major role in plasma-membrane resealing. Some patients with DYSF deletion mutations exhibit mild symptoms, suggesting some regions of DYSF can be removed without significantly impacting protein function. Antisense-mediated exon-skipping therapy uses synthetic molecules called antisense oligonucleotides to modulate splicing, allowing exons harboring or near genetic mutations to be removed and the open reading frame corrected. Previous studies have focused on DYSF exon 32 skipping as a potential therapeutic approach, based on the association of a mild phenotype with the in-frame deletion of exon 32. To date, no other DYSF exon-skipping targets have been identified, and the relationship between DYSF exon deletion pattern and protein function remains largely uncharacterized. In this study, we utilized a membrane-wounding assay to evaluate the ability of plasmid constructs carrying mutant DYSF, as well as antisense oligonucleotides, to rescue membrane resealing in patient cells. We report that multi-exon skipping of DYSF exons 26-27 and 28-29 rescues plasma-membrane resealing. Successful translation of these findings into the development of clinical antisense drugs would establish new therapeutic approaches that would be applicable to ∼5%-7% (exons 26-27 skipping) and ∼8% (exons 28-29 skipping) of dysferlinopathy patients worldwide. Keywords: exon skipping, antisense, morpholino, dysferlin, dysferlinopathy, limb-girdle muscular dystrophy type 2B, Miyoshi myopathy, distal myopathy, plasma membrane, membrane wounding